A multi-agents system for dynamic bus crew scheduling - Shibghatullah, Abdul Samad; Eldabi, Tillal; Rzevski, George; Razali, Sazalinsyah (2005)
Bus crew scheduling problem is remarkably difficult to solve because of the large number of resources that need to be allocated, very complex rules for the allocation of crew shifts, high cost of overtime and unpredictability of the urban trafﬁc and crew availability. Current schedulers are reviewed and critiqued. The paper considers an alternative approach to the bus crew allocation based on the use of Multi-Agent Systems (MAS) capable of real-time scheduling and dynamic re-scheduling whenever unpredictable events and change of resources or demands occurs.This paper proposes a conceptual framework for an optimum and dynamic crew scheduling by using the concept of MAS.